Impact of negative life events, self-esteem and social support on engagement in risky behaviors in adolescents : a longitudinal study. - Kwok, Kar Boon. (2009)
The current study examined the relationship between stressful life events, self-esteem, social support and engagement in risky behaviors in Canadian adolescents. A longitudinal design was utilized and studied whether stressful life events and engagement in risky behaviors are mediated by self-esteem. The study also examined whether the relationship between stressful life events and engagement in risky behaviors is moderated by social support. Results for the mediating model found a significant effect of self-esteem on the relationship between stressful life events and engagement in risky behaviors. However, no support was found for the moderated mediation model and social support was not found to significantly moderate the relationship between stressful life events and engagement in risky behaviors.